Efektivitas Terapi Psikoreligius Terhadap Pasien Dengan Halusinasi - Santi Rinjani; Murandari Murandari; Andri Nugraha; Efri Widiyanti (STIKes Karsa Husada Garut, 2021)
Abstract Hallucinations can cause behavioral changes such as aggressiveness, suicide, withdrawal from the environment, can harm yourself, others and the environment if you do not get treatment or further treatment. Therefore, psychoreligious therapy is used as an alternative by combining modern mental health approaches and religious or religious aspects that aim to improve coping mechanisms or overcome problems, especially hallucinations. This literature search aims to analyze the results of research that focuses on the effect of psychoreligious therapy on hallucinations. Method This study was carried out by reviewing the literature through electronic media on PubMed and Google Scholar and using the keyword psychoreligious therapy for hallucination, psychoreligious therapy in patients with hallucinations, after the search, there were 5 articles that met the criteria with a maximum publication year of the last 10 years. The results showed that psychoreligious therapy is a form of psychotherapy by combining a modern mental health approach and a religious or religious aspect approach that aims to improve coping mechanisms or solve a problem. During psychoreligious therapy, there was a decrease in the frequency of auditory hallucinations, a decrease in the hallucination score, and an increase in the ability to control hallucinations. There are three types of psychoreligious therapy, namely the dzkir method, reading the al-quran and reading the letter al fatihah. The conclusions in this study indicate that psychoreligious therapy is significantly effective in reducing the frequency of auditory hallucinations, decreasing hallucination scores, and increasing the ability to control hallucinations. Key words: psychoreligious therapy for hallucination, psychoreligious therapy in patients with hallucinations